2006
DOI: 10.1029/2006gl028448
|View full text |Cite
|
Sign up to set email alerts
|

Decontaminating tide gauge records for the influence of glacial isostatic adjustment: The potential impact of 3‐D Earth structure

Abstract: [1] We investigate the potential impact of lateral variations in mantle viscosity and lithospheric thickness on predictions of present-day relative sea-level change due to glacial isostatic adjustment (GIA). We consider three viscoelastic Earth models. The first is a 1-D model with a lithospheric thickness of 120 km and upper and lower mantle viscosities of 5 Â 10 20 Pa s and 5 Â 10 21 Pa s, respectively. The second model includes global lithospheric thickness variations and lateral heterogeneities in upper ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…As indicated in Figures 3 and S4, the greatest differences occur in locations proximal to the ice margin. These results are compatible with previous studies that considered the influence of lateral structure on rates of sea-level change at tide gauge stations [Kendall et al, 2006;Davis et al, 2008]. Our 3D model results also provide a partial explanation of why analyses based on 1D models (including this study) have not been capable of producing high quality fits at all locations along the U.S. Atlantic coast Roy and Peltier, 2015].…”
Section: Estimating Optimal Model Parameterssupporting
confidence: 91%
“…As indicated in Figures 3 and S4, the greatest differences occur in locations proximal to the ice margin. These results are compatible with previous studies that considered the influence of lateral structure on rates of sea-level change at tide gauge stations [Kendall et al, 2006;Davis et al, 2008]. Our 3D model results also provide a partial explanation of why analyses based on 1D models (including this study) have not been capable of producing high quality fits at all locations along the U.S. Atlantic coast Roy and Peltier, 2015].…”
Section: Estimating Optimal Model Parameterssupporting
confidence: 91%
“…Whitehouse et al (2006) showed that inclusion of 3D Earth structure perturbs uplift rate predictions across Fennoscandia by an amount greater than current GPS 585 accuracy, with significant implications for inferences of past ice-sheet history, while Kendall et al (2006) demonstrated that relative sea-level change predictions will be biased by >0.2 mm/yr at ~150 global tide gauge sites if 3D Earth structure is neglected, with maximum differences exceeding several mm/yr. Since solid Earth deformation depends on both the surface load history and Earth rheology, non-uniqueness is a problem when solving for these two unknowns.…”
Section: Gia Models Traditionally Assume the Earth Behaves As A Lineamentioning
confidence: 99%
“…Note that the sea level model is based on the "sea level equation" [43] and includes subsequent improvements to allow for coastline migration and changes in Earth rotation [44,45]. GIA models allow the calculation of vertical and horizontal land motion, sea level, gravitational, rotation and stress changes associated with a selected ice-Earth model combination.…”
Section: Glacial Isostatic Adjustment Modellingmentioning
confidence: 99%
“…The ice sheet, glacier and land water storage regional uncertainties are calculated by multiplying their global uncertainties by the respective normalized "sea level equation" patterns [43][44][45]. The methods used to compute uncertainties associated with GIA (obsvlm and gravgia) are given in Sections 2.1 and 3.1.…”
Section: Computing Regional Sea-level Projectionsmentioning
confidence: 99%